Chronic periodontitis and its correlation with socio-demographic and oral health parameters: a retrospective study in adults population - Yaacob, Munirah; Fazid, Nurul Farahin; So'odi, Siti Mahirah; Husain, Juzaily; Muhammad Ali, Suhaila (2018)
Introduction: Chronic periodontitis is the second most common oral disease worldwide. It is a multifactorial disease with bacterial plaque as the necessary factors but other factors such age, systemic conditions and social habits do play a determining role in the development of periodontitis. Therefore this study evaluated the correlation between severity of chronic periodontitis with a series of socio-demographic background and clinical variables. Materials and methods: This was a retrospective, observational study of chronic periodontitis population that attended IIUM Dental Clinic from the year 2014 to 2017. The data was extracted from patients’ case records systematically using structured data extraction form. Only case records with full clinical history and periodontal charting were undertaken as samples. IBM SPSS-24 was used for data analysis. x2 and Man Whitney U test was applied to infer the above relationship. Results: Over 4 years, 157 adults were diagnosed with chronic periodontitis, which comprised of 68.8% suffered with severe form. The mean age group was 48.6±11.55 with majority of them were Malays, male (p<0.05), and aged between 50 to 64 years old. Professional workers, those suffered with systemic diseases and were addicted to tobacco exhibited more severe disease though statistically not significant. Patients with moderate and severe chronic periodontitis showed greater plaque deposits and have deeper periodontal pockets than mild form (p<0.05). They also presented with more tooth lost. Conclusion: Severe chronic periodontitis was prevalent in the studied population. The clinical and socio-demographic characteristics showed non-significant correlation with severity of the disease except gender, plaque control levels, and number of deep sites. Future study should consider include more sample size from multicenter population.